2014
DOI: 10.1039/c4py00493k
|View full text |Cite
|
Sign up to set email alerts
|

Phosphazene-catalyzed ring-opening polymerization of ε-caprolactone: influence of solvents and initiators

Abstract: Metal-free ring-opening polymerization of ε-caprolactone was conducted using a relatively mild phosphazene base catalyst. The influence of solvents and protic initiators on the polymerization rate and control was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 56 publications
3
63
0
Order By: Relevance
“…Because the Huisgen 1,3‐dipolar cycloaddition reaction represents an efficient technique for the coupling of linear structures, well‐defined α‐azide, ω‐alkyne PCL‐ b ‐PL(D)LA linear copolymers have been prepared. By adapting the strategy developed by Hadjichristidis and co‐workers, those diblocks were obtained by sequential copolymerization of both ε‐caprolactone (CL) and lactide (LA) monomers from the 11‐azido‐1‐undecanol initiator while catalyzed by a P 2 ‐ t ‐Bu phosphazene base . Typically, the polymerization of CL is performed in THF ([CL] 0 ≈3 mol L −1 ) at r.t. for an initial monomer‐to‐initiator molar ratio ([CL] 0 /[I] 0 ) of 100.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the Huisgen 1,3‐dipolar cycloaddition reaction represents an efficient technique for the coupling of linear structures, well‐defined α‐azide, ω‐alkyne PCL‐ b ‐PL(D)LA linear copolymers have been prepared. By adapting the strategy developed by Hadjichristidis and co‐workers, those diblocks were obtained by sequential copolymerization of both ε‐caprolactone (CL) and lactide (LA) monomers from the 11‐azido‐1‐undecanol initiator while catalyzed by a P 2 ‐ t ‐Bu phosphazene base . Typically, the polymerization of CL is performed in THF ([CL] 0 ≈3 mol L −1 ) at r.t. for an initial monomer‐to‐initiator molar ratio ([CL] 0 /[I] 0 ) of 100.…”
Section: Resultsmentioning
confidence: 99%
“…By adapting the strategy developed by Hadjichristidis and co-workers, those diblocks were obtained by sequential copolymerization of both ε-caprolactone (CL) and lactide (LA) monomers from the 11-azido-1-undecanol initiator while catalyzed by a P 2 -t -Bu phosphazene base. [ 21 ] Typically, the polymerization of CL is performed in THF ([CL] 0 ≈3 mol L −1 ) at r.t. for an initial monomer-to-initiator molar ratio ([CL] 0 /[I] 0 ) of 100. After 4 h (Conv.…”
Section: Resultsmentioning
confidence: 99%
“…In that context, organocatalysts with low toxicity are of interest to achieve P(LA‐ co ‐CL)‐based materials. Attempts to use typical basic organocatalysts, such as phosphazenes, N ‐heterocycliccarbenes, or guanidine “superbases”, such as 1,5,7‐triazabicyclo[4.4.0]dec‐5‐ene did not enable to control the copolymerization of the two monomers. Acidic organocatalysts such as trifluoromethane sulfonic acid (TfOH) and (R)‐(−)‐1,1′‐binaphthyl‐2,2′‐diyl hydrogen phosphate (BPA) have also been used for this purpose .…”
Section: Methodsmentioning
confidence: 99%
“…The triblock terpolymers under study were synthesized previously, as reported in ref. . The structure of the PEO‐ b ‐PCL‐ b ‐PLLA triblock terpolymers are presented in Figure .…”
Section: The Abc Triple Crystalline Triblock Terpolymers Under Studymentioning
confidence: 99%